2023
DOI: 10.3389/fmolb.2023.1203208
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological effects and mechanisms of YiYiFuZi powder in chronic heart disease revealed by metabolomics and network pharmacology

Abstract: Introduction: YiYiFuZi powder (YYFZ) is a classical formula in Chinese medicine, which is commonly used clinically for the treatment of Chronic Heart Disease (CHD), but it’s pharmacological effects and mechanism of action are currently unclear.Methods: An adriamycin-induced CHD model rat was established to evaluate the pharmacological effects of YYFZ on CHD by the results of inflammatory factor level, histopathology and echocardiography. Metabolomic studies were performed on rat plasma using UPLC-Q-TOF/MS to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(8 citation statements)
references
References 70 publications
0
8
0
Order By: Relevance
“…Data-mining research has demonstrated that YYFZ can affect mitochondria-ER interactions by regulating mitochondrial function and ER function ( Wang, 2019 ; Wang Y. et al, 2023 ; Wang Y. Y. et al, 2023 ). In addition, network pharmacology has shown that YYFZ can modulate the phosphoinositide 3-kinase (PI3K)/AKT, modulating mitogen-activated protein kinase (MAPK), and Ras signaling pathways ( Wang Y. et al, 2023 ), all of which potentially affect mitochondria-ER interactions. Abnormal mitochondrial-ER interactions are thought to be key mechanisms in CVD such as CHD, HF, pulmonary hypertension, and atherosclerosis ( Zhang et al, 2020 ).…”
Section: The Impact Of Yyfz On Mitochondria-er Interactions Through D...mentioning
confidence: 99%
See 4 more Smart Citations
“…Data-mining research has demonstrated that YYFZ can affect mitochondria-ER interactions by regulating mitochondrial function and ER function ( Wang, 2019 ; Wang Y. et al, 2023 ; Wang Y. Y. et al, 2023 ). In addition, network pharmacology has shown that YYFZ can modulate the phosphoinositide 3-kinase (PI3K)/AKT, modulating mitogen-activated protein kinase (MAPK), and Ras signaling pathways ( Wang Y. et al, 2023 ), all of which potentially affect mitochondria-ER interactions. Abnormal mitochondrial-ER interactions are thought to be key mechanisms in CVD such as CHD, HF, pulmonary hypertension, and atherosclerosis ( Zhang et al, 2020 ).…”
Section: The Impact Of Yyfz On Mitochondria-er Interactions Through D...mentioning
confidence: 99%
“…Through metabolomics and network pharmacology analysis, it was found that YYFZ improves the efficiency of endoplasmic reticulum-associated protein degradation (ERAD), a process that removes misfolded proteins from the ER. By enhancing ERAD, it can reduce the accumulation of misfolded proteins and subsequently alleviate ER stress ( Wang Y. et al, 2023 ). ER stress is a cellular condition that occurs when there is an accumulation of unfolded or misfolded proteins in the ER ( Haeri and Knox, 2012 ), which triggers a cellular response known as the UPR ( Hetz, 2012 ).…”
Section: The Impact Of Yyfz On Mitochondria-er Interactions Through D...mentioning
confidence: 99%
See 3 more Smart Citations